Kajian Pembinaan, Pengembangan dan Pengawasan UKM Binaan PT Sucofindo - Musa Hubeis (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
Small and Medium Enterprises (SMEs) are 99.9% of total businesses in Indonesia. Mapping/clustering potential of SMEs that built in accordance with the conditions of the region/administrative, potential resources (commodities) and business units (production centers and groups) can be used as an indicator and the benchmark for guidance, development and supervision in order to strengthen the spine and the national economic structure. Objectives of the study are (1) identify potential SMEs that built in accordance with business information and problems encountered; (2) compile a database of selected target SMEs in the form of statistical profiles that are relevant to the purposes of guidance, development and supervision (success indicators and critical); (3) develop a standard model or alternative development, SMEs development and built a successful surveillance with the potential clustering patterns (base development) in accordance with local circumstances, and economic sectors. In this study used techniques: (1) desk research of secondary data sourced from SMEs that built by PT. Sucofindo and literature on SMEs-related studies conducted; (2) a brief survey to the selected SMEs locations from the point (1) purposively to obtain primary data as a verification activity that is supported by effective semi-structured questionnaire. Data analysis carried out descriptively, both qualitative and quantitative. From the study guidance, development and supervision of SMEs that built by PT Sucofindo available facts and data (information business, determinants, the feasibility of the business sector, loan repayment status and conceptual models) that SMEs that built can be categorized pre-enterprise SMEs and businesses running. Business grouping determines the smoothness of debt servicing. Therefore, in order to establish indicators of the model guidance, development and supervision in accordance with the type of SME, then the PT. Sucofindo requires an assessment system that is easy, fast, accurate, reliable and trustworthy, that can later be used as an effective guide for guidance, development and supervision of SMEs in general and in particular SMEs that built by PT. Sucofindo  used a generic approach in business performance indicators that are supported by indicators of business drivers. Model guidance, development and supervision SMEs that  has done so far by PT. Sucofindo still be reliable, but for the speed and feasibility of the establishment of SMEs which will be built into the front according to selected economic sectors, would be equipped with an approach that resulted in the studies of guidance, development and supervision, namely the general model of guidance, development and supervision of SMEs that built based on SMEs that built issues, systems of SMEs that built, assumptions, conceptual models and variables that can be measured. Guidance, development and supervision of SMEs that built, with potential cluster approach can be performed on: (1) category of solid natural resources, when positioned on the outskirts of the city and labor intensive, when positioned in the center of town; (2) technical assistance and competency-based according to the phase business. Both of the thing are helping improve the performance and structural improvement of SMEs, increase their competitiveness and resilience of SMEs supported by the core business, supporting business and related businesses intensively interconnected